(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Fine and coarse aggregates are the most common materials used in construction of cement concrete roads, alternate substitutes to coarse and fine aggregates like recycled aggregates and brick kiln powder have a prospect to replace fine and coarse aggregates in road constructions leading to effective cost-cutting, low pollution and comparable material strength. This work aimed to study the cost reduction of the cement concrete road and pollution caused by brick kiln powder and crushed aggregates and to see the strength properties of rigid pavement upon partial replacement. We achieved the study purpose by partially replacing the fine and coarse aggregate with brick kiln powder and recycled coarse aggregates. Subsequent analysis was performed by measuring various properties of brick kiln powder, admixture, fine aggregates, coarse aggregates, and recycled aggregates. Compressive strength and flexural strength tests were employed on the recycled coarse aggregates and brick kiln powder concrete mix. The results suggested the fact that a combination of brick kiln powder and recycled coarse aggregate as a replacement against conventional material is an effective material combination nearly as equivalent to the conventional concrete at replacements of 8% and 15%.